Non-Invasive Neuromodulation in the Rehabilitation of Pisa Syndrome in Parkinson's Disease: A Randomized Controlled Trial - De Icco, Roberto; Putortì, Alessia; Allena, Marta; Avenali, Micol; Dagna, Carlotta; Martinelli, Daniele; Cristina, Silvano; Grillo, Valentina; Fresia, Mauro; Bitetto, Vito; Cosentino, Giuseppe; Valentino, Francesca; et al. (Frontiers in Neurology, 2022)
Background Pisa syndrome (PS) is a frequent postural complication of Parkinson's disease (PD). PS poorly responds to anti-parkinsonian drugs and the improvement achieved with neurorehabilitation tends to fade in 6 months or less. Transcranial direct current stimulation (t-DCS) is a non-invasive neuromodulation technique that showed promising results in improving specific symptoms in different movement disorders. Objectives This study aimed to evaluate the role of bi-hemispheric t-DCS as an add-on to a standardized hospital rehabilitation program in the management of PS in PD. Methods This study included 28 patients with PD and PS (21 men, aged 72.9 ± 5.1 years) who underwent a 4-week intensive neurorehabilitation treatment and were randomized to receive: i) t-DCS (t-DCS group, n = 13) for 5 daily sessions (20 min−2 mA) with bi-hemispheric stimulation over the primary motor cortex (M1), or ii) sham stimulation (sham group, n = 15) with the same duration and cadence. At baseline (T0), end of rehabilitation (T1), and 6 months later (T2) patients were evaluated with both trunk kinematic analysis and clinical scales, including UPDRS-III, Functional Independence Measure (FIM), and Numerical Rating Scale for lumbar pain. Results When compared to the sham group, the t-DCS group achieved a more pronounced improvement in several variables: overall posture (p = 0.014), lateral trunk inclination (p = 0.013) during upright standing position, total range of motion of the trunk (p = 0.012), FIM score (p = 0.048), and lumbar pain intensity (p = 0.017). Conclusions Our data support the use of neuromodulation with t-DCS as an add-on to neurorehabilitation for the treatment of patients affected by PS in PD.